Perceived competencies and expected behaviour of a trainer in an education management training environment - Thanaraj, T. (University of Jaffna, 2012)
Since the changes in technology are intense and unprecedented in contemporary human history with its impact on almost all aspects of human life, organizations have invariably adopted training as a tool to fill the competency-gap of their employees to keep pace with such changes and also to enhance the employability of their employees in order to avoid extinction. They spend huge amount of resources to achieve this goal and for their survival. This additional emphasis on training has transformed training as a profession and the trainers as professionals. Hence, trainers need to possess a set of relevant competencies as well as acceptable behavioural patterns to be effective in their training activities. Education sector is no exception in this trend. This paper is an outcome of a study in which attempts were made to identify the essential competencies and behaviour of a trainer in an education management training environment in Sri Lanka as perceived by the participants of a particular training of a trainers (TOT) programme. Survey research design was applied among the sample which was a set of forty out of ninety six trainees in that programme with the questionnaire as main data collection tool. Further, sixteen experienced trainers were also interviewed and several sessions of the said TOT programme were observed. The study revealed that thorough knowledge of the subject or topic, strong communication skills and expertise in training methods particularly in andragogical methods are the three major competencies an effective trainer should possess. In terms of trainer’s expected behaviour in a training environment, five most important behavioural traits have surfaced in the study. They were: allow participants' to express their views; be friendly and humorous and keep the class lively; be thoroughly prepared and systematic in your delivery; integrate theory with practice and always maintain clarity in expression. The study also has brought out the important factors that make a training programme ineffective.
Keywords: Competencies; Behaviour; Training; Trainer